The 5α‐reductase inhibitor finasteride is not associated with alterations in sleep spindles in men referred for polysomnography. (23rd October 2015) - Goldstein, Michael R.; Cook, Jesse D.; Plante, David T.
Abstract : Objective: Endogenous neurosteroids that potentiate the gamma‐aminobutyric acid type A (GABAA ) receptor are thought to enhance the generation of sleep spindles. This study tested the hypothesis that the 5α‐reductase inhibitor finasteride, an agent associated with reductions in neurosteroids, would be associated with reduced sleep spindles in men referred for polysomnography. Methods: Spectral analysis and spindle waveform detection were performed on electroencephalographic (EEG) sleep data in the 11–16 Hz sigma band, as well as several subranges, from 27 men taking finasteride and 27 matched comparison patients (ages 18 to 81 years). Results: No significant differences between groups were observed for spectral power or sleep spindle morphology measures, including spindle density, amplitude, duration, and integrated spindle activity. Conclusions: Contrary to our hypothesis, these findings demonstrate that finasteride is not associated with alterations in sleep spindle range activity or spindle morphology parameters. Copyright © 2015 John Wiley & Sons, Ltd.